An uncommon hernia with an uncommon presentation: a case report on obturator hernia with ileal transection - S. P. Gayathre; D. Mugundhan; Baskaran, B. Aarthy (International Surgery Journal, 2023)
Obturator hernia is a rare pelvic hernia with an incidence of 1%. It is the protrusion of abdominal content through the obturator foramen. Here we report a rare case of obturator hernia in thin, emaciated female patient of age 60 years with complication of ileal transection, hence emphasizing early presentation and diagnosis.